PENGARUH AKUNTABILITAS, TRANSPARANSI, DAN PARTISIPASI ANGGARAN TERHADAP KINERJA ANGGARAN PADA PEMERINTAH KOTA DENPASAR - Premananda, Ni Luh Putu Uttari; Latrini, Made Yenni (E-Jurnal Akuntansi; Vol 18 No 3 (2017), 2017)
Accountability, transparency, and budgetary participation is a form of responsibility and openness in application of the budgeting  performance based on the value for money as core of performance measurement in government organization that provides budgetary performance that economical , efficiency, and effectiveness. Research is aimed to explain the impact of accountability, transparency, and budget ary participation on the performance of the budget. This research was conducted in local government of Denpasar in 2015. The sample of this research is the method of saturated samples. Methods of data collection is done by using a survey method and using the technique of Multiple Linear Regression Analysis. The analysis showed that accountability, transparency, and budgetary participation positively influence budget performance either partially or simultaneously in Denpasar government. Accountability, transparency and budgetary participation affect performance budget by 77.2 percent, while 2.8 percent remaining is influenced by other variables which not involved in the research model.
Keywords: budget performance, value for money, accountability, transparency, budgetary participation